When 'paradigms' differ: scientific communication between skepticism and hope in recent philosophy of science - Coletto, R. (Koers, 2008)
The first half of this article illustrates how contemporary humanist philosophy of science got caught up in a gradual loss of confidence concerning the possibility of sound communication among scholars holding on to different paradigms or presuppositions. The second half is dedicated to the responses provided by a Christian school of philosophy to the bleak possibility of a communication crisis. The resources deployed by the reformational school of philosophy are argued to constitute valuable instruments to create a more hopeful attitude towards scientific dialogue. A final note is dedicated to the possible causes of the difficulties experienced in this area of reflection by contemporary humanist philosophy of science.